Impacts of Inventory Management Factors on Inventory Performance Measures: The Sri Lankan Wholesale Sector - L. P. Hasindu Shanilka; C. A. Kavirathna (Journal of South Asian Logistics and Transport)
Inventory management is a crucial component of sustainability, enabling companies to reduce expenses, enhance cash flow, and increase profitability. Inventory makes up a majority of current assets in the wholesale sector, where inefficiencies are bound to happen, given the large-scale inventory. This research focuses on identifying the factors and performance measures of inventory management and evaluating their interrelationships focusing on the Sri Lankan wholesale sector. The factors identified through a systematic review and industry experts’ interviews were then categorized into key areas with a thematic analysis. The 22 factors identified were grouped into the categories of organization, facilities and equipment, and processes and practices. The 24 performance measures were grouped into operational, customer satisfaction, and environmental categories. A questionnaire survey was conducted with 126 managerial-level employees of wholesale organisations. The partial least squares structural equation modelling (PLS-SEM) method is used to validate the relationship between the variables and the moderation effect of firm size on these relationships. The findings reflect that factors of organisation and facilities and equipment, influence the performance measures. Organisational factors were the most significant in influencing all three performance categories. For most relationships, the firm size did not have a moderation effect. This research assists wholesale businesses in achieving excellence and a competitive edge in the Sri Lankan market while finding answers to the ongoing business issues in the wholesale sector.